Dampak dan Tantangan Pembelajaran Coding Bagi Siswa Sekolah Dasar: A Systematic Literature Review - Nur, Muhammad Awal; Nurhafidzah, Nurhafidzah (Jurnal Didaktika Pendidikan Dasar, 2025)
Coding education in elementary schools is increasingly important in developing 21st-century skills in students, including logical thinking, problem solving, and creativity. This study aims to identify, examine, and analyze the various impacts and challenges of implementing coding education for elementary school students based on previous research results. The research method used is Systematic Literature Review (SLR). Research data was obtained from academic databases, namely Google Scholar, SINTA-accredited journals, and Scopus, published between 2020 and 2025. Article data analysis used the PRISMA method with 5 inclusion criteria. The results of the study found 33 articles which were then analyzed and showed that the implementation of coding learning in elementary schools was through Scratch, Robotic Coding, Unplugged Coding, Code.org, and Augmented Reality. The impact of coding education on elementary school students includes improved computational thinking skills, increased creativity, improved science skills, planning skills, increased motivation to learn, improved critical thinking skills, improved academic achievement, improved problem-solving skills, and improved digital literacy. Meanwhile, the most frequently mentioned challenges were students’ difficulty in understanding abstract programming concepts, such as logic, algorithms, and variables, limitations in teacher training and infrastructure, and a lack of parental involvement. This study emphasizes the importance of a comprehensive approach in the form of developing a curriculum that is tailored to student characteristics, providing ongoing teacher training, providing adequate infrastructure, and involving parents and the community in supporting the learning process.